ANALISIS PENGEMBANGAN STRATEGI BERSAING MENGGUNAKAN PENDEKATAN META-SWOT PADA PT.ASTIKA MENTARI FARMA - Claudinia Cantika Olivia Laongan (Jurnal Ilmiah Mahasiswa FEB, 2019)
This study aims to find out and analyze the appropriate development of competitive strategies for PT. Astika Mentari Farma using Meta-SWOT approach that analyzes 2 environmental factors, i.e. internal factors using Resource-Based View analysis and external factors using PESTEL analysis. This research’s informants from PT.Astika Mentari Farma are director, head of finance, head of marketing, head of the repository, pharmacist, salesman, treasurer and customer. The informant from AMF’s biggest competitor (PT.Binasa) is director. Data obtained from direct observation, in-depth interview, questionnaires, the study of literature, and documentation. The result of the Resource-Based View analysis showed that PT. Astika Mentari Farma have 14 rare, inimitability and well managed resources and capabilities such as competitive sales price, cash and credit payment system, excellent service, brand awareness, personal selling, market expansion, main supplier, information technology, procurement management, quality assurance, employee training and development, skill of human relation, work culture, and employee loyalty. The result of PESTEL analysis showed that external factors that can give opportunity or threat for PT. Astika Mentari Farma is the great potential of the pharmaceutical industry, JKN program, and acceleration of restitution, new technology innovation platform, using environmentally friendly packaging, economic instability in Indonesia, poor control of medicine circulation from BPOM, and medicine sales regulation through online media. Based on Meta-SWOT analysis, PT. Astika Mentari Farma is in the first quadrant of the grand strategy matrix so the appropriate development competitive strategy to use are market penetration, market development, product development. PT. Astika Mentari Farma market penetration strategy is added employees, maintain sales price, and increase promotion. PT. Astika Mentari Farma market development strategy is to open a warehouse or office branch outside Makassar. PT. Astika Mentari Farma product development strategy is to add the types of medicine to sell. Keywords : Development Strategy, Competitive Strategy, Resource Based View, VRIO, PESTEL, Meta-SWOT